Pengaruh Sudut Masuk Impeller Terhadap Pola Alir Dalam Reaktor Biogas dengan Side Entering Mixer - Mochammad Murtadho; Yukh Ihsana; Ni’am Nisbatul Fathonah; Sugeng Winardi; Tantular Nurtono; Kusdianto . (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Side-entering impeller is widely used in the biogas plant. Liquid effluent is processed anaerobically in a hugetank with a relatively small impeller-to-tank diameter ratio.The purpose of this research is to study the sideeffects of entering angle against the flow characteristics in a stirred tank with side-entering mixers (SEM)using flow visualization techniques. This work was conducted on the tank cylinder with a diameter of 40 cmand 40 cm high liquid. Impeller 3-blade propeller which made from stainless steel with 3 and 4 cm indiameter. Variable speed rotary impeller used is 100 to 400 rpm. Side entry angle used are 5 °, 10 °, and 15 °right and left side.Visualization techniques used in this research, specifically focus on the light liquid layervertically and horizontally desired then photographed with a DSLR camera and observation in order tocharacterize the flow pattern. In the type of impeller propeller with an increase in rotational speed, thegeneral layout circulation flow getting to the top is almost half of the liquid level. The changes of side entryangle does not really give much influence over the location of the circulation flow that occurs in the tank.